2018
DOI: 10.7820/vli.v07.1.brown
|View full text |Cite
|
Sign up to set email alerts
|

Examining the word family through word lists

Abstract: The choice of lexical unit has important consequences for L2 vocabulary research, testing and instruction. In recent years, the most widely used lexical unit has been the word family. This study examines the characteristics of word lists based on the word family and explores the levels of text coverage such lists may provide should the assumption that learners can deal with word families be incorrect. This is pursued through the detailed examination of a set of word-family-based word lists. The study finds tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Headwords were chosen as the unit of counting for the target words because headwords are usually the most frequent members of word families, and thus the most likely members to be known. This is supported by a corpus-based study which indicated that the headword was the most frequent member of 82% of the most frequent 1,000 word families in Nation's (2006) British National Corpus word lists (Brown, 2018). Using headwords also reflects the nature of L2 teaching and learning (Brown, 2018;Dang & Webb, 2016).…”
Section: Target Wordsmentioning
confidence: 84%
See 1 more Smart Citation
“…Headwords were chosen as the unit of counting for the target words because headwords are usually the most frequent members of word families, and thus the most likely members to be known. This is supported by a corpus-based study which indicated that the headword was the most frequent member of 82% of the most frequent 1,000 word families in Nation's (2006) British National Corpus word lists (Brown, 2018). Using headwords also reflects the nature of L2 teaching and learning (Brown, 2018;Dang & Webb, 2016).…”
Section: Target Wordsmentioning
confidence: 84%
“…This is supported by a corpus-based study which indicated that the headword was the most frequent member of 82% of the most frequent 1,000 word families in Nation's (2006) British National Corpus word lists (Brown, 2018). Using headwords also reflects the nature of L2 teaching and learning (Brown, 2018;Dang & Webb, 2016). That is, L2 teachers and learners usually receive lists of headwords without their inflections and derivations, and, therefore, are most likely to choose headwords to teach and learn first.…”
Section: Target Wordsmentioning
confidence: 90%
“…Fifth, this study did not assess knowledge of word forms having multiple affixes. Brown (2018) reported that among types in the first 5,000 WF6s, 26.9% (inclusive of base words) had two or more affixes. Considering that such word forms could be more difficult to understand than words with a single affix, the present study may have overestimated learners’ ability to handle morphologically complex words in listening.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of 21 written texts, Laufer and Cobb (2020) found that derivational forms accounted for 7.78%, 7.88%, 5.04%, and 3.17% of the tokens in academic texts, newspaper articles, classic novels, and graded readers, respectively. Brown (2018) found that derivational forms comprised 13.4% of the coverage provided by the first five 1,000‐word bands of Nation's (2006a) BNC wordlists. We will use the figures from these two studies, together with data from McLean (2018) and Ward and Chuenjundaeng (2009) as previously presented, to estimate the amount of lost coverage due to unknown derivational forms in various discourse types.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation